Application of groundnut oil as plant based preservative to optimise postharvest quality of Padma 108 tomato fruits - Rahaman, A Abdul; Mahama, A P; Wahab, S A; Bashir, B; Nipurmeh, M; Adama, B A (Journal of Postharvest Technology, 2019)
Tomato fruits are cultivated across the regions in large and small scale quantities in sub Saharan Africa as food as well as economic crop. In Ghana, it is almost an obligatory ingredient in the daily diets of people across all regions. Tomato is consumed in diverse ways, including raw, as well as an ingredient in many dishes. The challenge however is the short shelf life which makes it difficult to preserve for longer duration resulting in lower return on investment. This research was carried out to examine how oil extracted from waste groundnut nut could be used to preserve Padma 108 variety of tomato fruits. Tomato fruits were held at 10ºC and 25ºC for 12 days after the application of plant based oil to compare with fruits without oil preservative. The experiment was laid out in Completely Randomized Design with three replications. Quality parameters assessed were Firmness, Total soluble solid, pH, percentage weight loss, taste and marketability. It was demonstrated that significant differences were found due to the variation in temperature in firmness and TSS at P ≤ 0.05 with fruits stored at 10°C showed firm texture and high TSS found at fruits held at 25°C. Preservative application also produced significant difference at P ≤ 0.05 in pH, weight loss, taste and marketability. Based on the findings from the research conducted, Padma 108 tomato variety quality can be optimized using combine effects of waste groundnut oil as plant based preservative and held at lower temperature.